Body dissatisfaction of women during postpartum period and copin strategies. (2nd January 2022) - Boybay Koyuncu, Saadet; Duman, Mesude
ABSTRACT: This descriptive, cross-sectional study examined body dissatisfaction and coping strategies of postpartum women. Women (n = 256) registered at a family health center in Turkey responded to a Participant Information Form and the Body Cathexis Scale between September 1 and December 31, 2020. The data were evaluated using the analyses of percentage, number, mean, standard deviation, Kruskal Wallis test, Mann Whitney U, Pearson correlation analysis, and Bonferroni tests. Women's dissatisfaction related to body image perception were associated with loss of physical strength, weight gain, hair loss, insomnia, change of breast shape, waist/back pain, facial spots, shape change in genitals, decrease in sexual activity and sexual desire, cellulite in the legs, and constipation. Regarding coping strategies, 8.4% women rested during the day to cope with the decrease in physical strength/fatigue they experienced, 44.5% followed a diet to cope with weight gain, 14% used shampoos and creams to cope with hair loss, 25.2% rested during the day to cope with insomnia, 36.8% wore a compression bra for their breasts, 12.4% exercised for waist/back pain. Findings indicate that postpartum women's average Body Cathexis Scale total score was low and that they experienced several issues regarding body image perception during this period.